2004
DOI: 10.1016/s0002-9440(10)63370-6
|View full text |Cite|
|
Sign up to set email alerts
|

Biological Significance of Focal Adhesion Kinase in Ovarian Cancer

Abstract: Focal adhesion kinase (FAK) is a nonreceptor tyrosine kinase that is activated by integrin clustering. There are limited data regarding the functional role of FAK in ovarian cancer migration and invasion. In the current study, FAK expression was evaluated in ovarian cell lines (nontransformed and cancer), 12 benign ovarian samples, and in 79 invasive epithelial ovarian cancers. All three ovarian cancer cell lines overexpressed FAK compared to the nontransformed cells. The dominant-negative construct called FAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
205
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(216 citation statements)
references
References 44 publications
11
205
0
Order By: Relevance
“…Finally, analyses of FAK expression levels in esophageal squamous cell carcinoma (Miyazaki et al, 2003), hepatocellular carcinoma (Itoh et al, 2004), acute myeloid leukemia (Recher et al, 2004) and ovarian cancer (Sood et al, 2004) tissue samples have found that FAK expression levels are inversely correlated with patient survival. As many cancer-related deaths are associated with elevated metastatic tumor burden, it is of interest to note that injection of malignant 4T1 cells expressing high levels of FAK led to the early death of 90% of injected animals within 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, analyses of FAK expression levels in esophageal squamous cell carcinoma (Miyazaki et al, 2003), hepatocellular carcinoma (Itoh et al, 2004), acute myeloid leukemia (Recher et al, 2004) and ovarian cancer (Sood et al, 2004) tissue samples have found that FAK expression levels are inversely correlated with patient survival. As many cancer-related deaths are associated with elevated metastatic tumor burden, it is of interest to note that injection of malignant 4T1 cells expressing high levels of FAK led to the early death of 90% of injected animals within 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…The biological importance of FAK-mediated signal transduction is underscored by the fact that this tyrosine kinase plays a fundamental role in embryonic development [11,12] and in the control of cell migration [9,[12][13][14][15][16][17][18][19], cell cycle progression [20] and apoptosis [21][22][23][24]. Furthermore, there is increasing evidence linking overexpression of FAK to the invasive properties of cancer cells [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of reports describe an enhanced expression of FAK protein in a variety of human cancers, including sarcomas, astrocytomas and carcinomas of the breast, colon, thyroid, prostate, oral cavity, liver, stomach and ovary (see (McLean et al, 2005) and references herein). Furthermore, FAK overexpression has been correlated with the invasive potential of a tumour and poor patient prognosis Miyazaki et al, 2003;Recher et al, 2004;Sood et al, 2004). In a study of 106 matched pairs of larynx carcinomas and corresponding normal tissue, using immunohistochemistry, we have previously shown a significantly increased expression of FAK at the protein level in both the tumour tissues and the corresponding metastasis (Canel et al, 2006).…”
mentioning
confidence: 99%